Exposure to pairs of Aeromonas strains enhances virulence in the Caenorhabditis elegans infection model - Mosser, Thomas; Talagrand-Reboul, Emilie; Colston, Sophie M.; Graf, Joerg; Figueras, Maria J.; Jumas-Bilak, Estelle; Lamy, Brigitte (Frontiers in Microbiology, 2015)
Aeromonad virulence remains poorly understood, and is difficult to predict from strain characteristics. In addition, infections are often polymicrobial (i.e., are mixed infections), and 5-10% of such infections include two distinct aeromonads, which has an unknown impact on virulence. In this work, we studied the virulence of aeromonads recovered from human mixed infections. We tested them individually and in association with other strains with the aim of improving our understanding of aeromonosis. Twelve strains that were recovered in pairs from six mixed infections were tested in a virulence model of the worm Caenorhabditis elegans. Nine isolates were weak worm killers (median time to death, TD50, ≥7 days) when administered alone. Two pairs showed enhanced virulence, as indicated by a significantly shortened TD50 after co-infection versus infection with a single strain. Enhanced virulence was also observed for five of the 14 additional experimental pairs, and each of these pairs included one strain from a natural synergistic pair. These experiments indicated that synergistic effects were frequent and were limited to pairs that were composed of strains belonging to different species. The genome content of virulence-associated genes failed to explain virulence synergy, although some virulence-associated genes that were present in some strains were absent from their companion strain (e.g., T3SS). The synergy observed in virulence when 2 Aeromonas isolates were co-infected stresses the idea that consideration should be given to the fact that infection does not depend only on single strain virulence but is instead the result of a more complex interaction between the microbes involved, the host and the environment. These results are of interest for other diseases in which mixed infections are likely and in particular for water-borne diseases (e.g., legionellosis, vibriosis), in which pathogens may display enhanced virulence in the presence of the right partner. This study contributes to the current shift in infectiology paradigms from a premise that assumes a monomicrobial origin for infection to one more in line with the current pathobiome era.